2020
DOI: 10.1038/s41598-020-72675-3
|View full text |Cite
|
Sign up to set email alerts
|

Collective photonic response of high refractive index dielectric metasurfaces

Abstract: Sub-wavelength periodic nanostructures give rise to interesting optical phenomena like effective refractive index, perfect absorption, cloaking, etc. However, such structures are usually metallic which results in high dissipative losses and limitations for use; therefore, dielectric nanostructures are increasingly considered as a strong alternative to plasmonic (metallic) materials. In this work, we show light-matter interaction in a high refractive index dielectric metasurface consisting of an array of cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
(58 reference statements)
2
14
0
Order By: Relevance
“…In our earlier work on periodic Te cubic arrays we observed that radiation-less anapole states are exhibited at 62 THz in air medium 50 . In the following sections we discuss in detail the effect of in-plane liquid crystal orientations on the anapole states in nematic medium.…”
Section: Electromagnetic Response As a Function Of Liquid Crystal Ori...mentioning
confidence: 83%
See 2 more Smart Citations
“…In our earlier work on periodic Te cubic arrays we observed that radiation-less anapole states are exhibited at 62 THz in air medium 50 . In the following sections we discuss in detail the effect of in-plane liquid crystal orientations on the anapole states in nematic medium.…”
Section: Electromagnetic Response As a Function Of Liquid Crystal Ori...mentioning
confidence: 83%
“…Figures 1c and 1d as S 12 = Te (ik 0 t) and S 11 = R, where R and T are reflection and transmission coefficients of medium, k 0 is the wave number in free space and t is the thickness of the dielectric layer, respectively. Scattering parameters exhibit a reflection band in the range 40 − 60 THz with two distinct peaks at both the ends in air medium 50 . Presence of nematic medium shifts the reflection band to lower frequencies (42-55 THz) with characteristic peaks varying as a function of LC orientation as shown in figures 1c and 1d.…”
Section: Electromagnetic Response As a Function Of Liquid Crystal Ori...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructured dielectric materials with high refractive index have emerged as a powerful toolkit for controlling light on the nanoscale, [56][57][58][59][60][61] and specifically for biosensing. [62][63][64][65] In contrast to plasmonic systems, where the optical response is dominated by electric multipoles, [22,66] resonances in dielectric particles readily support displacement currents driven by the incident light, allowing for the straightforward excitation of both electric and magnetic multipoles.…”
Section: Dielectricsmentioning
confidence: 99%
“…[ 19 ] Also, simpler systems were reported, where the point of darkness is achieved by the multistack made of, e.g., Ag (20 nm)/methyl methacrylate MMA (522 nm)/Ge (10 nm) Ag −1 (80 nm). [ 20 ] For our knowledge, there are relatively many publications for multilayer structures with the point of darkness at NIR and IR wavelength range, [ 19–25 ] and just few related to visible spectra range. [ 25,26 ] The reason is that the high efficiency absorption (at specific λ ) is mainly caused by the Fabry–Perot resonance in the non‐absorbing dielectric layer placed in the middle of the stack: that results in trapping of the resonant light in dielectric layer and thus in enhancement of absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%